DNA Based Identification and Phylogenetic Characterisation of Endophytic and Saprobic Fungi from Antidesma madagascariense, a Medicinal Plant in Mauritius. (27th May 2013) - Jeewon, Rajesh; Ittoo, Jayesh; Mahadeb, Devendra; Jaufeerally-Fakim, Yasmina; Wang, Hong-Kai; Liu, Ai-Rong
Abstract : Endophytes are fungi associated with plants without causing symptoms, and they are quite diverse and have enormous potential for production of important secondary metabolites for the pharmaceutical industry. In this study, we report for the first time fungi (both endophytes and saprobes) from Antidesma madagascariense, a medicinal plant in Mauritius, in view of identifying potential candidates for screening of fungi for pharmaceutical importance. In addition the phylogenetic placement of fungi recovered from leaves samples was investigated based on rDNA sequence analysis. Most commonly isolated fungi were related to Aspergillus, Guignardia, Fusarium, Penicillium, Pestalotiopsis, and Trichoderma . Phylogenetic analyses revealed that fungi recovered belong to 5 different fungal lineages (Hypocreaceae, Trichocomaceae, Nectriaceae, Xylariaceae, and Botryosphaeriaceae). DNA data from the ITS regions were reliable in classification of all recovered isolates up to genus level, but identification to an exact species name was not possible at this stage. Despite criticisms pertaining to the use of ITS sequence data in molecular systematics, our approach here provides an opportunity to justify the reliability of ITS sequence data for possible identification and discovering of evolutionary scenarios among isolates that do not sporulate under cultural conditions.